2020
DOI: 10.3389/fmicb.2020.00658
|View full text |Cite
|
Sign up to set email alerts
|

The Current and Future State of Vaccines, Antivirals and Gene Therapies Against Emerging Coronaviruses

Abstract: Emerging coronaviruses (CoV) are constant global public health threats to society. Multiple ongoing clinical trials for vaccines and antivirals against CoVs showcase the availability of medical interventions to both prevent and treat the future emergence of highly pathogenic CoVs in human. However, given the diverse nature of CoVs and our close interactions with wild, domestic and companion animals, the next epidemic zoonotic CoV could resist the existing vaccines and antivirals developed, which are primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
118
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 348 publications
(324 reference statements)
0
118
0
6
Order By: Relevance
“… Abstract Coronaviruses, including SARS-CoV-2 the etiological agent of COVID-19 disease, have caused multiple epidemic and pandemic outbreaks in the past 20 years 13 . With no vaccines, and only recently developed antiviral therapeutics, we are ill equipped to handle coronavirus outbreaks 4 . A better understanding of the molecular mechanisms that regulate coronavirus replication and pathogenesis is needed to guide the development of new antiviral therapeutics and vaccines.…”
mentioning
confidence: 99%
“… Abstract Coronaviruses, including SARS-CoV-2 the etiological agent of COVID-19 disease, have caused multiple epidemic and pandemic outbreaks in the past 20 years 13 . With no vaccines, and only recently developed antiviral therapeutics, we are ill equipped to handle coronavirus outbreaks 4 . A better understanding of the molecular mechanisms that regulate coronavirus replication and pathogenesis is needed to guide the development of new antiviral therapeutics and vaccines.…”
mentioning
confidence: 99%
“…The surface glycoproteins of the SARS-CoV-2 are the primary target for vaccine development. One of the primary goals of human COVID-19 vaccines is to elicit a strong humoral immune response against the S protein [ 275 ]. Moreover, MERS-CoV-specific CD4+ and CD8+ T cells are detected in peripheral blood mononuclear cells (PBMC) in MERS-CoV-infected survivors [ 276 ].…”
Section: Treatments For Covid-19mentioning
confidence: 99%
“…Developing treatment against SARS-CoV-2 will likely be useful for long-term protection, as it mutates slowly than the flu virus, so there is an urgent need for developing the vaccine. While live attenuated vaccines targeting respiratory viruses, including influenza viruses and adenoviruses, have been approved for use in humans, but these vaccines have the chance to revert back to the virulent strain [56] or recombination with parental/other strains [57] . Elaine et al, have shown the efficacy of live attenuated strain lacking E-gene against SARS-CoV-1 infections in syrian golden hamsters [58] .…”
Section: Management and Treatment Optionsmentioning
confidence: 99%